Augmented Reality Enhances Indonesian Nursing Students’ Knowledge and Motivation in Open Fracture Learning - Rismawan Yunanto; Baskoro Setioputro; Ruris Haristiani; Nur Safira (JKG (JURNAL KEPERAWATAN GLOBAL), 2025)
Background: Open fracture cases have complex management that involves bleeding control based on comprehensive knowledge and training. Augmented Reality (AR) offers an interactive learning approach that may enhance nursing students' motivation and knowledge of emergency open fracture cases. This study aims to evaluate the effectiveness of augmented reality in improving the knowledge and learning motivation of Indonesian nursing students regarding open fracture learning. Methods: This study used a cluster randomized pretest–posttest control group design involving four class groups of nursing students (n = 155). Two clusters received the Open Fracture Augmented Reality Application, while two received conventional lectures. Motivation was measured using the validated MSLQ, and knowledge using a 29-item validated questionnaire. Both groups completed pretest and posttest assessments. Data were analyzed using descriptive statistics, Wilcoxon, and Mann–Whitney tests (α = 0.05). Results: A total of 155 nursing students participated, with balanced baseline characteristics between groups. The AR intervention significantly improved knowledge (p = 0.001, r = 0.38) and motivation (p = 0.022, r = 0.27) in the intervention group, while no significant gains occurred in the control group. Between-group analysis showed higher posttest knowledge in the AR group (p = 0.005), indicating that AR was more effective than conventional instruction, particularly for cognitive outcomes. Conclusion: Augmented Reality–based learning significantly improves nursing students’ knowledge of open-fracture management compared with traditional methods, while showing no significant between-group differences in motivation, highlighting AR’s value as an effective supplemental tool for enhancing understanding of complex clinical content.